2015
DOI: 10.1007/s00394-015-0947-5
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of oxidative and inflammatory status in hearts of cholesterol-fed rats supplemented with oils or oil-products with extra virgin olive oil components

Abstract: Overall, we suggest that the EVOO-polar phenolic compounds decreased MDA and TNF-α in hearts of cholesterol-fed rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 59 publications
3
19
0
Order By: Relevance
“…Based on previous investigations, plant sterols lower the LDL cholesterol level, with no impact on the HDL cholesterol or triglyceride concentrations [3,6]. Further, in the present study, HDL cholesterol concentrations did not differ between treatments, while TG levels were found to be higher in the HCD-treated groups compared with the controls, which could be attributed to the method used for inducing the hypercholesterolemia, in line with other studies [17].…”
Section: In Vivo Studysupporting
confidence: 92%
See 1 more Smart Citation
“…Based on previous investigations, plant sterols lower the LDL cholesterol level, with no impact on the HDL cholesterol or triglyceride concentrations [3,6]. Further, in the present study, HDL cholesterol concentrations did not differ between treatments, while TG levels were found to be higher in the HCD-treated groups compared with the controls, which could be attributed to the method used for inducing the hypercholesterolemia, in line with other studies [17].…”
Section: In Vivo Studysupporting
confidence: 92%
“…Previous studies have shown that the lipid matrix and nature of the colloidal interactions operating between oil droplets considerably affects the stability of lipid nanoparticles [10][11][12][13][14][15][16][17][18][19][20]. In this study, wax-based NLCs were stabilized by Tween 80 and lecithin.…”
Section: Physical and Chemical Stabilitymentioning
confidence: 88%
“…A shorter period (4 weeks) required the concomitant administration of 0.1% astaxanthin to induce superoxide dismutase and glutathione peroxidase activities in male KK‐A (y) mice fed a high fat/sucrose diet despite the use of 2% squalene . Likewise, the decrease in malondialdehyde in hearts was observed in Wistar rats fed a high cholesterol diet supplemented with 10% extra virgin olive oil for 9 weeks . These findings emphasize the crucial role of experimental design in terms of dose, time period, and animal model.…”
Section: Squalene and Cardiovascular Diseasementioning
confidence: 72%
“…The Mediterranean diet, which is rich in olive oil, is associated with the reduction in mortality from cardiovascular diseases, cancer risk and skin wrinkling . In addition, aged rats fed lifelong with olive oil present the lowest number of histological, molecular and biochemical alterations in heart, liver and pancreas throughout the ageing process . These studies indicate that oral administration of olive oil may be the better option to attenuate the signs of skin ageing.…”
Section: Discussionmentioning
confidence: 89%